1999
DOI: 10.1046/j.1365-2249.1999.00999.x
|View full text |Cite
|
Sign up to set email alerts
|

An African green monkey lacking peripheral CD4 lymphocytes that retains helper T cell activity and coexists with SIVagm

Abstract: Natural infection with simian immunodeficiency virus (SIV) is known to occur in the African green monkey (AGM). The actual onset of the disease has not been recognized in SIVagm infected AGM, and the precise reason for such apathogenicity in the AGM remains unclear. We reported previously that AGM peripheral CD4 lymphocytes underwent a peculiar differentiation from CD4+ to CD4- cells after in vitro activation, and we inferred that the AGM does not fall into a fatal immunodeficient state because of the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 44 publications
2
34
0
Order By: Relevance
“…Consistent with previous studies (7,25), the SIV Gag-specific T cell response was not of exceptional magnitude, and the immune response to SIV clearly was not able to fully control viremia in the study animals. Instead, it is clear that natural host species are able to avoid progressive disease despite ongoing viral replication.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Consistent with previous studies (7,25), the SIV Gag-specific T cell response was not of exceptional magnitude, and the immune response to SIV clearly was not able to fully control viremia in the study animals. Instead, it is clear that natural host species are able to avoid progressive disease despite ongoing viral replication.…”
Section: Discussionsupporting
confidence: 89%
“…Adult AGMs have low CD4 ϩ T cell counts (4,5) and a large population of CD8␣ dim T cells that express CD8␣␣ homodimers and are distinct from the classical CD8 T cells that express the ␣ and ␤ chain of CD8 (4,6,7). These CD8␣␣ T cells arise postthymically through CD4 downregulation by CD4 ϩ T cells (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in some contexts, CD8 dim T cells substituted for CD4 + T cells and provided B cell help, leading to antibody production (48,49). Other studies showed that type 2 polarization of CD8 + T cells induced epigenetic modifications on the CD8α locus, resulting in downregulation of CD8 surface expression in mice (32).…”
Section: Consistent With Our Findings Are Reports That Cd8mentioning
confidence: 99%
“…It is possible that HIV-1 may be able to infect other lymphoid cells through a CD4-independent mechanism (as has been suggested for the infection of astrocytes in the central nervous system), or it may target cells that transiently express CD4 during maturation or activation. Many investigators have provided evidence for the widespread infection in vitro and in vivo of human CD8 ϩ , cytotoxic T lymphocytes by HIV-1 (16,30,32,34,50,54) or by the primate simian immunodeficiency virus (SIV) homologues SIV mac in sooty mangabeys (12) and SIV agm in African green monkeys (37). Infection of cells destined to become CD8 lymphocytes may occur through a conventional CD4-dependent mechanism during their maturation in the thymus, at the stage where CD4 is coexpressed with CD8 (12,24).…”
mentioning
confidence: 99%